Charles William Dyson Perrins as a Collector of Medieval and Renaissance Manuscripts c. 1900-1920 - Laura Cleaver (Perspectives Médiévales)
The manuscript collection of Charles Dyson Perrins is well known among scholars, in large part due to the publication of an imposing and detailed catalogue by George Warner in 1920. Perrins has become associated with spending large sums of money on manuscripts and the account of his purchase of the Gorleston Psalter following a visit to a bookshop in search of something to read on the train is a legend of the trade. The first sale of his manuscripts after his death in 1958 achieved a record total. However, like most early twentieth-century collectors, Perrins’ catalogue only contains a selection of the manuscripts that passed through his hands. Reconstructing the larger collection therefore sheds light on the choices made in creating and publishing parts of his manuscript collection. Perrins began collecting manuscripts as an extension of his interest in early printed books and maintained a strong interest in late medieval and renaissance manuscripts. The influence of a small group of collectors and scholars, and in particular Sydney Cockerell, helped shape Perrins’ manuscript collection and publicise it through its use as the basis for the Burlington Fine Arts Club exhibition of illuminated manuscripts in 1908 and the creation of monographs on particular volumes as well as the 1920 catalogue. In contrast, only part of the printed collection ever received a published catalogue. Cockerell may also have been involved in Perrins’ decision to sell some of his manuscripts, anonymously, in 1907. These decisions have had significant consequences for the long-term ownership of and scholarship on these manuscripts, and provide a case study of the impact of early twentieth-century collectors on the development of the study of medieval books.